Chemical constituents and antioxidant activity from the fruits of phaleria macrocarpa (scheff.)boerl - Khaw, Swee Por, 1990-; Norazah Basar; Fakulti Sains (2014)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2014